2018
DOI: 10.1007/s40265-018-0947-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Risk of Rhabdomyolysis and Myopathy During Concomitant Treatment with Ticagrelor and Statins

Abstract: The introduction of ticagrelor, one of the first directly-acting oral antiplatelet drugs, provided new possibilities in the prevention of thrombotic events in patients with acute coronary syndromes (ACS). Current guidelines recommend ticagrelor in dual antiplatelet therapy with aspirin over clopidogrel for prevention of stent thrombosis in patients with ACS. Moreover, in the management of ACS, lipid-lowering treatment with high-intensity statin therapy is advised for secondary prevention of cardiovascular even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 63 publications
1
37
0
4
Order By: Relevance
“…MNK treatment (10 mg/kg) for 7 days led to significant antioxidant, anti-inflammatory and reduction in AST and ALT in a rat model for lipopolysaccharide-induced toxicity (Mohamadin et al, 2011). The Statins can cause different degrees of muscle injury and inflammation which may result in renal injury (Danielak et al, 2018). The results of the present study showed that MNK and SMV treatments increased myoglobin and creatinine levels significantly compared to control group.…”
Section: Livermentioning
confidence: 47%
See 2 more Smart Citations
“…MNK treatment (10 mg/kg) for 7 days led to significant antioxidant, anti-inflammatory and reduction in AST and ALT in a rat model for lipopolysaccharide-induced toxicity (Mohamadin et al, 2011). The Statins can cause different degrees of muscle injury and inflammation which may result in renal injury (Danielak et al, 2018). The results of the present study showed that MNK and SMV treatments increased myoglobin and creatinine levels significantly compared to control group.…”
Section: Livermentioning
confidence: 47%
“…Statins can cause different degrees of muscle injury and inflammation which may result in renal injury (Danielak et al, ). The results of the present study showed that MNK and SMV treatments increased myoglobin and creatinine levels significantly compared to control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The authors have mentioned that in cases where Ticagrelor was used they monitored the creatinine. Recently there has been a spate of cases 7,8 where ticagrelor has caused rhabdomyolysis when used in conjunction with statins. Thus, it is pertinent that we are aware of this devastating complication while using this particular drug.…”
mentioning
confidence: 99%
“…Thus, for the authors and any such cases, an alternative of Fluvastatin, which is metabolized by P450 CYP2C9, is suggested. While it is routinely safe to use the 2 drugs together, caution may be advisable, especially in elderly cases, 8 as most of the ages reported were above 60 years, and the author population reported the age range was wide (20-75 years). Also, it might be advisable to monitor cases with creatinine kinase and myoglobin values rather than creatinine alone, as they might be more specific.…”
mentioning
confidence: 99%